Covid-19—a rehearsal to build a greener and healthier society. (28th January 2021) - Nilsson, Maria; Ebi, Kristie L; Campbell-Lendrum, Diarmid; Kone, Brama; Friberg, Peter
Abstract : Maria Nilsson and colleagues argue that reducing the severe health risks from the climate crisis requires political commitment and funding like that mobilised to limit the spread of SARS-CoV-2